Implementing Sustainable Practices in the Cardiac Catheterization Laboratory: Results from a Year-Long Waste Reduction Initiative - Chen, Kuan-Jen; Chen, Lung-Ching; Liou, Jer-Young; Hung, Huei-Fong; Lin, Shen-Chang; Shyu, Kou-Gi; Lee, Shih-Huang; Chang, Che-Ming; Chao, Shu-Ping; Wang, Tzu-Lin; Wei, Cheng-Chun; Liao, Zhen-Yu; et al. (Acta Cardiologica Sinica, 2025)
Background: Cardiac catheterization laboratories (CCLs) contribute significantly to hospital waste and environmental impact. While sustainability efforts in healthcare are growing, comprehensive strategies for waste reduction in CCLs remain limited. Aims: This study evaluated the effectiveness of a quality improvement initiative in reducing waste output and enhancing recycling practices in a high-volume CCL. Methods: A one-year study was conducted in a single-center CCL performing approximately 2,800 annual procedures. Interventions included staff education, waste tracking, improved segregation, forming a sustainability team, and regular progress updates. Waste outputs were measured at baseline, one month, three months, and one year post-intervention. Carbon footprint reductions were calculated using emission factors of 340.00 kg/ton of carbon dioxide equivalent (tCO_2e) for incinerated waste and 0.11 kg/tCO_2e for recyclable glass. Results: Over one year, infectious waste decreased by 35.4% [from 2.38 ± 0.40 to 1.54 ± 0.09 kilogram per procedure (kg/procedure)], and general waste decreased by 26.4% (from 0.83 ± 0.14 to 0.61 ± 0.03 kg/procedure). Recyclable paper increased by 55.5% (from 0.30 ± 0.05 to 0.47 ± 0.03 kg/procedure). The estimated annual carbon footprint reduction was 1,084.2 kg carbon dioxide equivalent. Conclusion: Sustainability initiatives can significantly reduce waste and carbon emissions in CCLs while promoting recycling. This study provides a practical framework for advancing environmental sustainability in high-volume CCLs.